Households or Locations? Cities, Catchment Areas and Prosperity in India - Li, Yue (World Bank E-Library Archive, 2015)
It also finds that top locations and their catchment areas include many high-performing rural places, and are not necessarily more unequal than average locations. Preliminary analysis reveals that these top locations and their catchment areas display characteristics that are generally believed to drive agglomeration economies and contribute to faster productivity growth